Crystal structure of aqua-2,2′,2′′-(((nitrilo-κN-tris(ethane-2,1-diyl))tris(azanylylidene-κ3N′,N′′,N′′′))tris(methanylylidene))tris(4-chlorophenolato-κ3O,O′,O′′)neodymium(III), C27H26Cl3N4NdO4 - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (de Gruyter, 2019)
C27H26Cl3N4NdO4, monoclinic, P21/c (no. 14), a = 13.6408(1) Å,b = 20.3377(2) Å, c = 10.7272(1) Å, β = 109.896(1)°, V = 2798.34(5) Å3, Z = 4, Rgt(F) = 0.0258, wRref(F2) = 0.0590, T = 100(2) K. CCDC no.: 1902338 The molecular structure is shown in the figure. Table 1 contains crystallographic data and Table 2 contains the list of the atoms including atomic coordinates and displacement parameters.